Pengaruh Free Cash Flow dan Leverage terhadap Kinerja Keuangan dengan Likuiditas sebagai Pemoderasi pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Mia Agustina Natalia Putri; Sri Yuni; Agus Kubertein; Oktobria Y. Asi; Christina Fransiska; Iwan Christian (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to examine the effect of free cash flow and leverage on financial performance with liquidity as a moderating variable in consumer goods industry companies listed on the IDX in 2020-2022. The population in this study are consumer goods industrial companies listed on the IDX in 2020-2022. The sampling method uses purposive sampling with a final sample size of 31 companies. The data analysis technique uses the help of the SPSS application program version 25. The data analysis technique in this research uses descriptive statistics, classical assumption tests, multiple regression analysis, moderated regression analysis and hypothesis testing using the t test and coefficient of determination test. The test results show that free cash flow has a positive and significant effect on financial performance, while leverage has no significant effect on financial performance. Liquidity as a moderator weakens the influence of free cash flow on financial performance, while liquidity can strengthen the influence of leverage on financial performance.